Case Report: Challenges of orthodontic treatment in patients with autism spectrum disorders diagnosed in adulthood - Motoko Watanabe; Chihiro Takao; Chizuko Maeda; Ikuo Yonemitsu; Yasuyuki Kimura; Risa Tominaga; Takahiko Nagamine; Takahiko Nagamine; Takashi Ono; Akira Toyofuku (Frontiers in Psychiatry)
Patients with autism spectrum disorders (ASDs) occasionally have difficulties in dental settings owing to specific features, including hypersensitivity and restrictive persistence. When features of ASD remain unnoticed until adulthood, dental procedures would be provided without considering the patient’s potential ASD traits. Herein, we present three cases of ASD diagnosed in adulthood that experienced difficulties during orthodontic treatment, resulting in unsatisfactory outcomes, and discuss the importance of planning treatment and management that takes their ASD features into consideration. Case 1 involved a 23-year-old man who complained of unstable occlusion for three years since the initiation of orthodontic treatment and required orthodontic retreatment to return to his previous dentition. Previous orthodontic treatments had been discontinued on some occasions because of the hospitalized pharmacotherapy for exacerbated psychiatric conditions. Case 2 involved an 18-year-old woman who complained of unbearable changes in dentition in her upper incisors and changed facial appearance during orthodontic treatment, which caused her to drop out of school. Case 3 involved a 41-year-old woman who complained of a sliding jaw, especially when wearing a retainer, and changes in facial appearance for five years following the alignment of her dentition. All cases experienced discomfort and exacerbation of psychiatric conditions that were diagnosed as ASD during orthodontic treatment. Their complaints of persistent discomfort, including intolerance to the changed occlusion or facial appearance, would relate to their features of ASD, including hypersensitivities and restricted and repetitive behaviors. A vicious cycle between the exacerbation of their psychiatric conditions and uncomfortable sensations would impede the satisfactory goals of orthodontic treatment. Indications for orthodontic treatment should be carefully discussed, and treatment management that considers the characteristics of ASD, especially those that were diagnosed in adulthood, is crucial. This case series highlights the necessity of multidisciplinary follow-up throughout the long-term orthodontic treatment period in this patient population.